Sejarah Salah Satu Kota Kolonial di Jawa Tengah “Semarang” - Firmanda Dwi Septiawan (Program Studi Pendidikan Sejarah Universitas Riau, 2022)
The city of Semarang has experienced a long historical journey. The current form of Semarang is the result of changes over time. Semarang is the capital of Central Java province, as the provincial capital of course Semarang has faster progress compared to other cities in Central Java. Since colonial times, Semarang has indeed developed into a developed and crowded city. The history of Semarang began more or less in the 8th century AD, namely a coastal area called Pragota (now Bergota) and was part of the ancient Mataram kingdom.